From Serviced Sites to Peripheral Tenements: A Long-Arc History of Chennai's Unaffordable Housing. (November 2022) - Coelho, Karen; Srivathsan, A.; Pattnam, Gayathri
Housing policies in India tend to reduce the urban housing challenge to a volumetric problem of increasing stock, particularly in the 'affordable' category, and increasingly by 'crowding in private investment'. This standardised policy agenda has overwritten local histories and sociological understandings of housing as embedded in social relations. The singular focus on facilitating private markets in affordable housing is everywhere confounded by contextual factors that determine local geographies of housing, land markets and parameters of affordability. What explains the conspicuous absence of private builders in Chennai's affordable housing market, despite strong demand in this segment and over two decades of state policies aimed at incentivising their participation in this market? This article proposes that a long-range history of Chennai's settlement and land use shifts, social/demographic changes, and housing policies from the early twentieth century can provide clues towards understanding its current housing market, and can contribute policy-relevant insights that expand the question of urban housing beyond measures of stocks and prices to qualitative concerns. The article employs archival material (including government reports, plans, policies and media reports) and primary data from a recent study by the authors on the supply, location and prices of current affordable housing stock in Chennai.